Impact generated by the unification of the mandatory health plan in the public social companies (2013)
In 2012 the unification of the mandatory Health Plan Subsidized Regime which equals the provision of health services with the same rights in the contributory system procedures, interventions, consultations were made; and expanding coverage to this population ensuring comprehensive care. This unification gender impact on the finances of public institutions because much of the population went from user linked by the Local Authorities who were paying for these services through the supply subsidy to be subsidized users charge of the Health Promoting Companies of the subsidized those who do not generate cash flows in a timely manner affecting liquidity, financial sustainability and development of the constitutional mission of these entities. Also affects the user population for the delay in the authorization of services demand.